Desenvolvimento de aplicativo para estimativa de propriedades volumétricas, residuais e termodinâmicas e avaliação de equações cúbicas de estado - Oliveira, Levi Gomes de (2017)
The volumetric, residual and thermodynamic properties are essential to design, assessment, simulation and optimization of several existing equipment at chemistry and petrochemical industry. These types of industrial equipment operate through of changes in the primary variables (thermodynamic potential), from one state to another. In order to evaluate the heat quantities and work involved in a determined industrial process, the chemical engineer needs experimental data of volumetric, residual and thermodynamic properties; these properties only are available to some commonly used fluids, such as water, refrigerants and cryogenic fluids (fluid with normal boiling temperature less than 123,5 K). Nowadays, commercial software utilized various methods of calculus of volumetric, residual and thermodynamic properties related to pure substances and mixtures, for example: ASPEN-HYSYS, CHEMCAD, PROSIM, etc. These programs are characterized by initial great investment due to budget the license of the software (out of reality from the most of Brazilian university, essentially from North-Northeast universities) and high computational complexity. Evidently, the efficient use of these programs requires knowledge from the employed methodology, which are not accessible to the user (black box). For so, these cited software hinder its use for educational purposes due to the lack of experience from the students. Based on the above considerations, an EXCEL/VBA software was proposed to be able of estimating volumetric, residual and thermodynamic properties through following cubic equations of state: van der Waals, Redlich-Kwong, Soave-Redlich-Kwong, Wilson, Peng-Robinson and Patel-Teja. Furthermore, it is proposed to the developed application to make such estimates in a simple, efficient and reliable way. In addition, the developed software had being validated through available data in the open literature. From the application program, it was studied the performance of the cubic equations addressed in this work. For last, still it is possible to design valves and turbines/expanders using cubic equations.